2023
DOI: 10.1002/cbdv.202200518
|View full text |Cite
|
Sign up to set email alerts
|

[3+2] Cycloaddition Synthesis of New Piperazine‐Linked Bis(chromene) Hybrids Possessing Pyrazole Units as Potential Acetylcholinesterase Inhibitors

Abstract: Two series of piperazine-linked bis(chromene) hybrids that are attached to pyrazole units were synthesized in the current study. Both series are attached to an acyl unit at pyrazole-C3, with one series attached to an acetyl unit and the other to an ethoxycarbonyl unit. A [3 + 2] cycloaddition protocol was conducted to produce the target hybrids with good yields by reacting the appropriate hydrazonoyl chlorides with chromene-based bis(enaminone) in dioxane containing triethylamine at reflux for 4 h. New hybrids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…In fact, the chemical and structural characteristics of AChE inhibitors that are similar to those of nefazodone have been studied in recent years. 21,22) Next, we investigated the rhAChE inhibitory activities of 21 hypnotics and 12 anxiolytics at 10 −4 M, which is higher than their CABCR (Supplementary Tables 5, 6). [11][12][13][23][24][25][26][27][28] We found that two hypnotics (triazolam and brotizolam) and one anxiolytic (buspirone) inhibited rhAChE activity by ≥20%.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the chemical and structural characteristics of AChE inhibitors that are similar to those of nefazodone have been studied in recent years. 21,22) Next, we investigated the rhAChE inhibitory activities of 21 hypnotics and 12 anxiolytics at 10 −4 M, which is higher than their CABCR (Supplementary Tables 5, 6). [11][12][13][23][24][25][26][27][28] We found that two hypnotics (triazolam and brotizolam) and one anxiolytic (buspirone) inhibited rhAChE activity by ≥20%.…”
Section: Discussionmentioning
confidence: 99%
“…Table 4 demonstrates We recently discovered that bis-analogues may have more effective bioactivity than mono-analogues. [39,55] The current study successfully prepared three new series of bis(pyrazolo[1,5-a]pyrimidines) 10, 12, and 14. In each series, the two pyrazoloquinazoline units are linked at C9 by an appropriate spacer attached to two o-or p-phenoxy groups.…”
Section: Chemistryselectmentioning
confidence: 95%
“…[32,33] Much effort has been made by our research group to prepare new azoloazines with promising antibacterial activity. [34][35][36][37][38][39] In this context, we reported herein the development of a three-component protocol to synthesize arene-linked pyrazolo [5,1-b]quinazolines and their bisanalogues (see Figure 2). The antibacterial activity of the new products was screened against different ATCC bacterial strains.…”
Section: Introductionmentioning
confidence: 99%
“…[21,32] In this study, we aimed to develop facile methods to produce two series of pyrazolo [1,5-a]pyrimidines as part of our ongoing research to synthesize pyrazole-fused azines with potential bioactivity, specifically antibacterial activity (see Figure 2). [33][34][35][36][37][38] The new compounds were evaluated as potential antibacterial agents, and their pharmacological properties and drug-like characteristics were predicted using SwissADME and a drug-likeness model score.…”
Section: Introductionmentioning
confidence: 99%